(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Behavioral finance is the study of psychological biases which influences the decision making process of investors. Most of the theories of finance and economics are based on two common assumptions viz. human is rational and is involved in informed decision making. Contrary to this, the behavioral finance focuses more on the irrationality of human behavior. The investors as human beings have varied number of emotions which divert them from rational decision making and create market anomalies. The classical finance assumes investors as a rational agent while behavioral finance called them irrational. As a result a new paradigm known as behavioral finance has been developed. In this paper an attempt is made to highlight the shortcomings of the traditional finance theories as pointed out by behavioral finance supporters and also a discussion on the significance of behavioral finance. This paper discusses new approach, i.e. behavioral finance in the world of financial markets.